Job Security and Work Absence: Evidence from a Natural Experiment - Assar Lindbeck; Mårten Palme; Mats Persson (Research Institute of Industrial Economics (IFN), 2006)
We analyze the consequences for sickness absence of a selective softening of job security legislation for small firms in Sweden in 2001. According to our differences-in-difference estimates, aggregate absence in these firms fell by 0.2-0.3 days per year. This aggregate net figure hides important effects on different groups of employees. Workers remaining in the reform firms after the reform reduced their absence by about one day. People with a high absence record tended to leave reform firms, but these firms also became less reluctant to hire people with a record of high absence.
Keywords: H53; I38; J22; J50; M51; 330; Seniority Rules; Sick Pay Insurance; Firing Costs; Moral Hazard; Kündigungsschutz; Fehlzeit; Krankheit; Moral Hazard; Wirkungsanalyse; Schweden